2018
DOI: 10.6000/1929-7092.2018.07.08
|View full text |Cite
|
Sign up to set email alerts
|

New Meaningful Effects in Modern Capital Structure Theory

Abstract: Paper is devoted to describe the new meaningful effects in capital structure theory, discovered within modern theory of capital cost and capital structure, created by Brusov, Filatova and Orekhova (BFO theory). These qualitatively new effects are present in general version of BFO theory and absent in its perpetuity limit (Modigliani-Miller theory). BFO theory has changed some main existing principles of financial management. Discovered effects modify our understanding of financial management and dictate some u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…However, the bankruptcy of trade-off theory has been proven by Brusov et al in 2013 [14] within the Brusov-Filatova-Orekhova (BFO) theory [15][16][17][18][19][20][21]. They have shown that the suggestion of risky debt financing (and growing credit rate near the bankruptcy) surprisingly does not lead to growing of weighted average cost of capital (WACC), with leverage level: WACC still decreases with leverage level.…”
Section: Introduction 1literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the bankruptcy of trade-off theory has been proven by Brusov et al in 2013 [14] within the Brusov-Filatova-Orekhova (BFO) theory [15][16][17][18][19][20][21]. They have shown that the suggestion of risky debt financing (and growing credit rate near the bankruptcy) surprisingly does not lead to growing of weighted average cost of capital (WACC), with leverage level: WACC still decreases with leverage level.…”
Section: Introduction 1literature Reviewmentioning
confidence: 99%
“…(in the presence of corporative taxes). As was shown, a lot of qualitatively new effects in corporate finance, obtained within Brusov-Filatova-Orekhova theory [14][15][16][17][18][19][20][21], are absent in Modigliani-Miller theory [1][2][3][4]. The Brusov-Filatova-Orekhova formula for WACC has the following form:…”
Section: Introduction 1literature Reviewmentioning
confidence: 99%
“…But the methodologies of leading rating agencies, such as "The Big Three credit rating agencies" (Standard & Poor's (S&P), Moody's, and Fitch Group) as well as Russian rating agency ACRA and all other ones have a lot of shortcomings. A number of works by authors are devoted to eliminating some of these shortcomings (Brusov et al, 2018(Brusov et al, , 2018a(Brusov et al, , 2018b(Brusov et al, , 2018c(Brusov et al, , 2018d.…”
Section: Introductionmentioning
confidence: 99%
“…But the methodologies of leading rating agencies, such as "The Big Three credit rating agencies" (Standard & Poor's (S&P), Moody's, and Fitch Group) as well as Russian rating agency ACRA and all other ones have a lot of shortcomings. A number of works by authors are devoted to eliminating some of these shortcomings (Brusov et al, 2018(Brusov et al, , 2018a(Brusov et al, , 2018b(Brusov et al, , 2018c(Brusov et al, , 2018d.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the fact, that RA represent some "black boxes", the information about the methods of work of which is almost completely absent, there are some serious methodological and systematic errors in their activity. These errors and ways to their overcome have been discussed in a number of authors papers (Brusov et al, 2018(Brusov et al, , 2018a, as well as in monograph (Brusov et al, 2018).…”
Section: Introductionmentioning
confidence: 99%